ISOLASI DAN UJI PATOGENITAS JAMUR Colletotrichum spp. PENYEBAB PENYAKIT ANTRAKNOSA PADA BUAH TOMAT (Solanum lycopersicum L.) : ISOLATION AND PATHOGENITY TESTING OF FUNGI Colletotrichum spp. CAUSES OF ANTHRACNOSE DISEASE ON TOMATOES (Solanum lycopersicum L.) - Laila Maghfirotun Ni’mah; Sang Ketut Sudirga; Anak Agung Ketut Darmadi (SIMBIOSIS, 2025)
Tomatoes (Solanum lycopersicum L.) is a fruit with important economic value and is a leading horticultural commodity in Indonesia. Anthracnose is a disease that can infect tomato plants. From previous research, several types of isolates of Colletotrichum spp. Infecting different hosts can cause different disease severity. The aim of this research was to identify the Colletotrichum fungus that causes anthracnose on tomatoes from several gardens in Bali to test its level of pathogenicity. Isolation of the fungus Colletotrichum spp. using the direct planting method. The pathogenicity test uses the disease severity (KP) scoring method using the formula. Identification and morphological characterization of isolates of Colletotrichum spp. using the identification book "Illustrated Genera of Imperfect Fungi". The parameters observed were colony shape, hyphae and conidia characters and disease severity percentage (KP) on tomatoes. This research used a completely randomized design (CRD) and the data were analyzed statistically using the ANOVA (Analysis of Variance) test with SPSS version 26 software. The results of the identification of macroscopic and microscopic characters from PS, BS and SW isolates showed differences in colony, hyphae and conidia characters. The pathogenicity test results of the PS, BS, and SW isolates showed that the SW isolate was the most adaptive and pathogenic isolate. Keywords: Identification, isolate, hyphae, spores, disease severity